The nonvesicular sterol transporter Aster-C plays a minor role in whole body cholesterol balance - Banerjee, Rakhee; Hohe, Rachel C.; Cao, Shijie; Jung, Bryan M.; Horak, Anthony J.; Ramachandiran, Iyappan; Massey, William J.; Varadharajan, Venkateshwari; Zajczenko, Natalie I.; Burrows, Amy C.; Dutta, Sumita; Goudarzi, Maryam; et al. (Frontiers in Physiology, 2024)
The Aster-C protein (encoded by the Gramd1c gene) is an endoplasmic reticulum (ER) resident protein that has been reported to transport cholesterol from the plasma membrane to the ER . Although there is a clear role for the closely-related Aster-B protein in cholesterol transport and downstream esterification in the adrenal gland, the specific role for Aster-C in cholesterol homeostasis is not well understood. Here, we have examined whole body cholesterol balance in mice globally lacking Aster-C under low or high dietary cholesterol conditions. Methods: Age-matched Gramd1c +/+ and Gramd1c -/-mice were fed either low (0.02%, wt/wt) or high (0.2%, wt/wt) dietary